Procedural Formalities versus Substantive Protection (Reconciliation and Child Welfare in Divorce under Algerian and Indonesian Legal Systems) - Yassine Chami; Elsa Rina Maya Toule; Deassy Jacomina Anthoneta Hehanussa; Mohammad Abdallah Alshawabkeh; Driss ED Daran; Enas Qutieshat; Muhamad Haviz (IAIN Manado, 2026)
This study aims to analyze the role of judges in promoting reconciliation and protecting children's rights during divorce proceedings, as regulated by the Algerian Family Code and the Civil and Administrative Procedure Code. The research employs a normative legal approach by examining statutory provisions and relevant literature to evaluate the practical implementation of legal norms. The findings reveal that although reconciliation is mandated by law, the failure to undertake such efforts does not invalidate the divorce judgment. This suggests that reconciliation serves as a procedural formality rather than a substantive requirement within the legal framework. The research further underscores the need for a more integrated legal approach that balances legal certainty with child protection. In practice, judicial focus during reconciliation hearings tends to prioritize the interests of the divorcing parties while insufficiently addressing the implications for children. Consequently, the study emphasizes the importance of active judicial intervention to safeguard children's rights to custody, maintenance, and protection during divorce. It advocates for legal reform to transform reconciliation into a meaningful mechanism, ensuring that the child's best interests are at the center of divorce proceedings.